2014
DOI: 10.1016/j.exer.2013.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptors in whirler mice show defective transducin translocation and are susceptible to short-term light/dark changes-induced degeneration

Abstract: Usher syndrome combines congenital hearing loss and retinitis pigmentosa (RP). Mutations in the whirlin gene (DFNB31/WHRN) cause a subtype of Usher syndrome (USH2D). Whirler mice have a defective whirlin gene. They have inner ear defects but usually do not develop retinal degeneration. Here we report that, in whirler mouse photoreceptors, the light-activated rod transducin translocation is delayed and its activation threshold is shifted to a higher level. Rhodopsin mis-localization is observed in rod inner seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Originally, the USH2 complex at the periciliary membrane complex was proposed to participate in protein trafficking through the connecting cilium [107], but no clear evidence demonstrates any defects in protein trafficking between the inner and outer segment in Ush2a −/− and Whrn neo/neo photoreceptors [106, 116]. Interestingly, using Whrn wi/wi mice, which do not develop spontaneous retinal degeneration [106], Tian et al demonstrated a defect in light-induced transducin translocation from photoreceptor outer to inner segment and light-induced retinal degeneration [160]. The molecular mechanisms underlying these phenotypes in Whrn wi/wi mice need to be further elucidated.…”
Section: Functional Studies Of Ush Gene Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, the USH2 complex at the periciliary membrane complex was proposed to participate in protein trafficking through the connecting cilium [107], but no clear evidence demonstrates any defects in protein trafficking between the inner and outer segment in Ush2a −/− and Whrn neo/neo photoreceptors [106, 116]. Interestingly, using Whrn wi/wi mice, which do not develop spontaneous retinal degeneration [106], Tian et al demonstrated a defect in light-induced transducin translocation from photoreceptor outer to inner segment and light-induced retinal degeneration [160]. The molecular mechanisms underlying these phenotypes in Whrn wi/wi mice need to be further elucidated.…”
Section: Functional Studies Of Ush Gene Productsmentioning
confidence: 99%
“…Further, cadherin 23, harmonin and clarin-1 proteins of various species show significantly different retinal cellular and subcellular patterns [97, 99, 112, 114, 115, 118, 119]. A third hypothesis is that light illumination is necessary to induce retinal degeneration in USH mouse models [153, 160], although the underlying mechanism is unclear. Recently, zebrafish models carrying USH gene mutations have emerged to exhibit early retinal degeneration phenotypes, such as myo7aa ty229d/ty229d and ush1c fh293/fh293 zebrafish [115, 151], indicating that zebrafish models could be useful for understanding functions of USH genes in the retina and testing potential treatments.…”
Section: Current Gaps In Understanding and Treating Ushmentioning
confidence: 99%
“…Dark-rearing has also been demonstrated to delay PR degeneration in Slc6a6 tm1Dhau (10% loss vs. 90% loss in normal vivarium lighting at three weeks of age) [473] or have no effect in C57BL/6-Mitf mi-vit /J homozygotes [474]. In some situations, light may actually trigger the disease phenotype, as is the case in Sag knockout mice [198,199], with three Class B1 Rhodopsin missense mutations, Tvrm1 and Tvrm4 [157] or Tvrm144 [18], and in null mutation models of Rdh12 [475], Asic2 [476], Myo7a [477], Whrn [478], or Akt2 [479]. Sag mutants must be reared in the dark to observe any PR cells.…”
Section: Effects Of Environment On Pr Degenerationmentioning
confidence: 99%
“…For example, transgenic mice expressing a mutant form of the α‐subunit of transducin (Tα), in which Tα acylation and localization to the outer segment are inhibited, show a decreased light sensitivity of rod photoreceptors (Kerov et al , ). In contrast, mouse lines modeling Usher syndrome, shaker1 and whirler , exhibit defective Tα translocation to the inner part and a decreased threshold of light‐triggered photoreceptor degeneration (Peng et al , ; Tian et al , ). Furthermore, additional lipid modification by an amino acid substitution partially blocks light‐induced Tα translocation from the outer segment to the inner part, leading to photoreceptor cell death (Kerov & Artemyev, ; Majumder et al , ).…”
Section: Introductionmentioning
confidence: 99%